2020
DOI: 10.1123/ijspp.2018-0914
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of a Ceiling Effect for Training Volume in Muscle Hypertrophy and Strength in Trained Men—Less is More?

Abstract: Purpose: To compare the effects of different resistance training volumes on muscle performance and hypertrophy in trained men. Methods: Thirty-seven volunteers performed resistance training for 24 weeks, divided into groups that performed 5 (G5), 10 (G10), 15 (G15), and 20 (G20) sets per muscle group per week. Ten-repetition maximum (10RM) tests were performed for the bench press, lat pulldown, 45° leg press, and stiff-legged deadlift. Muscle thickness was measured using ultrasound at biceps brachii, triceps b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…This might be important to consider in programming in order to avoid potential overtraining or performance of unnecessary training volume. It is important point out, that there are a compelling evidences for an upper threshold for RT volume regarding RT adaptations [27,35,36], therefore, if an excessive volume is performed by a cer-tain muscle group it might lead to overtraining, or at the least constitute a potential waste of time.…”
Section: Discussionmentioning
confidence: 99%
“…This might be important to consider in programming in order to avoid potential overtraining or performance of unnecessary training volume. It is important point out, that there are a compelling evidences for an upper threshold for RT volume regarding RT adaptations [27,35,36], therefore, if an excessive volume is performed by a cer-tain muscle group it might lead to overtraining, or at the least constitute a potential waste of time.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, consequently, generate better anabolic responses in the presence of adequate recovery 10,11 . In fact, the literature has shown that higher training volumes have provided high myofibrillar protein synthesis responses 12 and several chronic studies support higher training volume by maximizing muscle hypertrophy. This has been suggested in a recent meta-analysis 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…One objective variable that indirectly quantifies mechanical tension within a session is the volume load (sets × reps × load kg). While there is some controversy [9,10], it has been suggested that producing greater training volumes per session would optimize muscle mass accrual [5,11]. Additionally, the literature also suggests that other factors associated with metabolic stress (i.e.…”
Section: Introductionmentioning
confidence: 99%